2021
DOI: 10.1055/s-0041-1733923
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Mortality after Venous Thromboembolism: A Meta-Analysis of Prospective Cohort Studies

Abstract: Many studies from current literature show that cardiovascular diseases in patients with venous thromboembolism (VTE) are more frequent than in the general population without VTE. However, data summarizing the impact of cardiovascular diseases on mortality of patients with VTE are lacking. In this systematic review and meta-analysis, we aimed to determine the frequency and incidence rate of cardiovascular death in patients with VTE. MEDLINE and EMBASE were searched from January 1, 2000 to February 28, 2021. Eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Similarly, pooled data from the prospective Cardiovascular Health Study (CHS) and the Atherosclerosis Risk in Communities (ARIC) Study show a moderately increased risk of VTE in older adults with OH [55], while thromboembolic complications in AF patients have been extensively reported by Rubart et al [56]. A recent meta-analysis by Noumegni et al shows that over 35% of deaths among VTE patients were attributable to cardiovascular deaths [57].…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, pooled data from the prospective Cardiovascular Health Study (CHS) and the Atherosclerosis Risk in Communities (ARIC) Study show a moderately increased risk of VTE in older adults with OH [55], while thromboembolic complications in AF patients have been extensively reported by Rubart et al [56]. A recent meta-analysis by Noumegni et al shows that over 35% of deaths among VTE patients were attributable to cardiovascular deaths [57].…”
Section: Discussionmentioning
confidence: 94%
“…Noumegni et al also performed a meta-analysis of 13 studies to evaluate the risk of cardiovascular death after VTE. 14 The follow-up varied between 1 and 60 months in the studies. Approximately one-third of the recorded deaths was classified as cardiovascular, which was higher than in a population that had not had VTE.…”
Section: Robert Louis Stevenson 1850-1894mentioning
confidence: 99%
“…9 Moreover, the authors were able to compare frequency of CVDT in patients with VTE and in controls without VTE in two studies and they found a pooled risk ratio of 3.85, which was statistically significant. 9 10 11…”
Section: Introductionmentioning
confidence: 96%
“…9 Moreover, the authors were able to compare frequency of CVDT in patients with VTE and in controls without VTE in two studies and they found a pooled risk ratio of 3.85, which was statistically significant. [9][10][11] In the goal to reduce the incidence of arterial cardiovascular events and the incidence of recurrent VTE, which are the most frequent causes of CVDTs in patients with VTE, several studies explored the risk factors of these events in patients with VTE. [12][13][14][15][16][17] Despite the fact that the great majority of these studies did not consider the impact of non-CVDT as potential competing events to their outcome of interest, they allowed a considerable progress in the prevention of all cardiovascular events after VTE.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation